EPHX1 rs2234922 polymorphism and lung cancer susceptibility in Asian populations: a meta-analysis - Xu, Xuefang; Hua, Hongxia; Fan, Bing; Sun, Qing; Guo, Xuedan; Zhang, Jiawei (Journal of Thoracic Disease, 2015)
Objective: Polymorphisms of epoxide hydrolase 1 (EPHX1) rs2234922 have been reported to be associated with variations in EPHX1 activity. Many studies have investigated the association between EPHX1 rs2234922 polymorphism and lung cancer risk, but their results have been inconsistent. The purpose of this study was to perform a meta-analysis of all eligible studies to derive a more precise estimation of the associations of EPHX1 rs2234922 polymorphism with lung cancer. Methods: The PubMed was searched for case-control studies published up to Oct 01, 2014. Data were extracted and pooled odds ratios (ORs) with 95% confidence interval (CI) were calculated. The pooled ORs for the risk associated with the genotypes of homozygote G/G and G allele carriers (A/G + G/G) with the A/A genotype were calculated. Heterogeneity assumption was checked by the chi-square-based Q-test. A P value greater than 0.10 for the Q-test indicates a lack of heterogeneity among studies, so the pooled OR estimate of the each study was calculated by the fixed-effects model (the Mantel-Haenszel method). Otherwise, the random-effects model (the DerSimonian and Laird method) was used. Results: In this meta-analysis, we assessed eight published studies involving comprising 1,175 cases and 1,550 controls of the association between EPHX1 rs2234922 polymorphism and lung cancer risk. For the homozygote G/G and G allele carriers (A/G + G/G), the pooled ORs were 1.47 (95% CI: 1.18-1.79, P=0.007 for heterogeneity) and 1.36 (95% CI: 1.14-1.62, P=0.828 for heterogeneity), when compared with the homozygous wild-type genotype (A/A). Conclusions: EPHX1 rs2234922 polymorphism contributes to risk of lung cancer among Asian population.